Keragaman Curah Hujan Antar Tahun dan Dampaknya terhadap Pola Tanam di Kabupaten Malang, Indonesia - Aris Pramudia; Suciantini Suciantini; Elsa Rakhmi Dewi; Dede Dirgahayu Domiri; Erni Susanti; Rita Indrasti; Robi Muharsyah; Darmawan Lahru Riatma; Abriani Fensionita; Yunita Fauziah Rahim; Misnawati Misnawati; Yudi Riadi Fanggidae (Buitenzorg: Journal of Tropical Science, 2026)
El Niño and La Niña events typically affect rainfall patterns and water availability for plants, especially in rainfed and upland farming systems. This study examines year-to-year variations in rainfall associated with El Niño and La Niña events, as well as their impacts on potential planting seasons and the management of food crop planting patterns in Malang Regency. The rainfall data used in this analysis are from the Karangploso and Karangkates climatology stations for the period 2012-2024. The analysis reveals that over the past 13 years, El Niño events have not shifted the duration of the dry or rainy seasons in Lawang Subdistrict, nor have they reduced the rainy-season duration by 1 decade compared to normal conditions in Donomulyo Subdistrict. However, La Niña events can prolong the rainy season by 3-13 decades in Lawang Subdistrict or 2-14 decades in Donomulyo Subdistrict. The average potential planting time at the research location is 210 days in Lawang Subdistrict and 240 days in Donomulyo Subdistrict, posing a significant risk of planting rice across two growing seasons. By selecting adaptive crops and managing planting patterns, it could be possible to plant three times using a rice-corn-beans pattern during the planting seasons in the Lawang Subdistrict or a rice-corn and rice-beans pattern in the Donomulyo Subdistrict. During La Niña events, crop pattern management can be more flexible, and planting intensity can be increased by 3-4 times through effective crop pattern management.